Socio-economic conditions and agricultural water management practices of smallholders in Quaternary Catchment B72A, Olifants River Basin, South Africa - (:unkn) unknown (My University, 2008)
This report synthesizes the results of research undertaken under the Challenge Program Water and Food on socio-economic conditions and water management practices of smallholders in the Olifants river basin of South Africa. It is mainly based on field work conducted in the B72A quaternary catchment of the basin, the focus of field studies for several research projects of IWMI. Primary data were collected in 2005 through three households surveys on: i) land and water management practices of farmers, ii) the impact of socio-economic conditions and water management on food security of households, and iii) the viability of small-scale irrigation farms. Secondary data from the 2001 Census, reports from NGO working in the study site, research reports on similar issues conducted in neighbouring districts, and previous research by IWMI in the Olifants River basin were also used. Data analysis is based on the sustainable livelihood approach and comprises the construction of a typology of farm-household systems based on their livelihood activities and asset endowments. Results include the presentation of demographic characteristics of households, their livelihood activities, water sources, uses and management, agricultural production and farming practices including access to markets, and food security status, and the presentation of the typology of farming households.
Keywords: African Research